THE INFLUENCE OF SALES GROWTH, COMPANY SIZE AND FIXED ASSET INTENSITY ON TAX AVOIDANCE - Handayani, Puspita; Ratnasari, Fina; Nursita, Meta (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
In Indonesia, inconsistencies frequently arise between the planned tax revenue and budgeting and the actual realization, with tax avoidance being a notable contributing factor. Tax avoidance refers to a company's lawful attempts to decrease tax payments by exploiting legal loopholes. While it is within legal bounds, widespread utilization of this practice by numerous companies can adversely impact government tax revenues, leading to substantial losses for the country. The objective of this research is to examine and assess the impact of sales growth, company size, and fixed asset intensity on tax avoidance. The research employs a causal approach, utilizing secondary data. Documentation method was employed for data collection, sourced from the Indonesian Stock Exchange (www.idx.co.id). The study population consists of Property and Real Estate companies listed on the IDX from 2017 to 2022, totaling 97 companies. Purposive sampling was employed, resulting in a sample size of 66. Descriptive statistical analysis, panel data regression model estimation, classical assumption tests, and goodness of fit model tests were employed for data analysis using the Eviews 12 program. The findings reveal no significant influence of sales growth on tax avoidance, while company size and fixed asset intensity exhibit a noteworthy impact. Simultaneously, all tested independent variables exhibit a positive effect on tax avoidance. The coefficient of determination for the research model is 38.55%. Suggestions for future research include incorporating additional independent variables and, if feasible, intervening and moderating variables related to tax avoidance.